On indications for repeat liver transplantation - V. V. Borovik; I. I. Tileubergenov; O. A. Gerasimova; D. A. Granov (Вестник трансплантологии и искусственных органов)
Objective: to study the causes of graft loss and indications for repeat liver transplantation (rLT).Materials and Methods. We studied the experience garnered from 250 orthotopic full-size cadaveric liver transplantations in 228 patients from 1998 to 2021. The severity of the patient’s condition at the time of intervention was estimated according to the MELD scale. Repeat surgeries were performed in 22 cases in 19 patients (analyzed group).Results. Organ preservation parameters, length of stay in intensive care unit (ICU), severity of postoperative complications in primary transplantations in general and in the analyzed group did not differ significantly. The main causes of graft loss were graft arterial insufficiency (57.9%) and hepatic artery thrombosis (21%). Severe early allograft dysfunction (EAD) and primary nonfunction accounted for 10.5%, portal vein thrombosis occurred in 5%, and chronic graft rejection was noted in 5% of cases.Conclusion. Arterial insufficiency is one of the leading causes of graft loss after liver transplantation. Early correction of arterial and biliary complications help in preserving graft viability.